THE PROFILE OF COLORECTAL ADENOCARCINOMA AT DR. M. DJAMIL GENERAL HOSPITAL PADANG, INDONESIA - Liana, Nana; Helmizar, Roland; Ruhsyahadati, Ruhsyahadati; Jelmila, Sri Nani; Triyana, Rahma; Lismawati, Lismawati (Yayasan Nusantara Hasana Berdikari, 2024)
Colorectal carcinoma is the third most common malignancy in the world. This malignancy originates from the epithelium of the colon and/or rectum, showing glandular or mucinous differentiation, where tumor cells have penetrated the muscularis mucosae layer. The study aims to report on epidemiological, clinical, and pathological characteristics of colorectal adenocarcinoma. Methods: We performed a retrospective descriptive study of 140 cases of colorectal adenocarcinoma in the gastroenterology and general surgery departments of M. Djamil General Hospital Padang, Indonesia conducted from January 2022 to December 2022. Data collection using medical records of patients in M. Djamil General Hospital Padang, Indonesia. We reported different data: Age, sex, site, and differentiation grade of the tumor. Results: Our study included 140 patients 80 males (57,1%) and 60 females (42.9%), with a median age range of 51-60 years. The tumors were found in the rectum 82 (58.6%), distal colon 37(26.4%), and proximal colon 21(15.0%). The differentiation grade was majority low grade 117 (83.6%). Conclusion: In conclusion, our result showed that colorectal adenocarcinoma is highest in the male population with an age range of 61-70 years. The most common site of adenocarcinoma is rectum. A low grade is the most differentiated grade. Keywords: colorectal adenocarcinoma, anatomical location, differentiation grade, profile